Agroindustrial productivity through copra processing partnership mechanisms in Bulukumba, South Sulawesi, Indonesia - Firdausi, Ananda Nuril; Bakhtiar, Ary; Agustina, Yohana; Akbar, Adjar Yusriandi (AGROMIX, 2025)
Introduction: the expanding demand for copra (the dried flesh of a coconut), the desiccated kernel of the coconut fruit, underscores its promising potential for agroindustrial development. Effective partnership formations emerge as pivotal drivers in this context. This study aims to ascertain the most productive partnership patterns within five distinct mechanisms operating in Bulukumba, South Sulawesi, Indonesia. Methods: the research site was determined using a purposive method, selecting five sub-districts prominent for coconut production, and employing the snowball sampling technique for data collection. Productivity analysis was conducted utilizing efficiency criteria and profit ratios across various partnership patterns. Results: efficiency and profit ratios were calculated for each mechanism as follows: 1) middlemen involvement yielded an efficiency of 107% and a profit ratio of 0.94; 2) engagement with local traders resulted in 77% efficiency and a profit ratio of 1.29; 3) participation in farmers' associations exhibited 36% efficiency and a profit ratio of 2.76; 4) group mechanisms demonstrated 86% efficiency and a profit ratio of 1.17; while 5) subcontract mechanisms displayed 31% efficiency and a profit ratio of 3.24. Conclusion: among the investigated mechanisms, the subcontract mechanisms emerged as the most productive partnership model, while the middlemen mechanism, non-partnership, exhibited the lowest productivity.